COVID-19, ODONTOSTOMATOLOGY OROFACIAL FINDINGS OF INTEREST - Innocenti, Ezequiel (2021)
The emergence of the coronavirus 2019 (COVID-19) reform a new global strategy for world health and life. Its detection or premature diagnosis has become vital to be able to control its dynamics as a pandemic. This virus is transmitted from human to human through droplets and direct contact with the oral, nasal and ocular mucous membranes, even some studies suggest that it can be airborne through aerosols. This fact encourages epidemiological and clinical researchers to establish highly sensitive case definitions to track all true positive cases; therefore, there is emerging evidence of oral lesions that may be indicative of viral pathology. The purpose of this review article is to provide documentary support that aims to raise awareness among dental professionals that a careful orofacial examination is mandatory, especially when dealing with suspected patients infected with SARS-CoV-2 or not, in order to further enrich the report of possible specific and nonspecific signs and symptoms of the current global pathology and enrich the scientific knowledge for its final control and eradication.